SURVEI KEKUATAN OTOT KAKI PADA ANAK TUNA GRAHITA DI SLB EKA MANDIRI KOTA BATU MALANG - Bagus Kurniawan; Saichudin Saichudin; Rias Gesang Kinanti (Universitas Negeri Malang, 2017)
Abstract The objective of the study was to know the level of leg muscle strength in the mentally disabled child's. Later will be known how the level of leg muscle strength is the same as a normal child or not. Research on leg muscle strength test in SLB Eka Mandiri Batu Malang, using qualitative research. Qualitative research is part of qualitative research. The research procedure that produces descriptive data in the form of oral or written words of the people or behavior observed. Approach directed background and individual as a whole.Results test with leg dynamometer states that the level of leg muscle strength. Mental disability with mild and moderate mentally disabled different, although the level of physical activity is the same but from the level of muscle strength of the mentally disabled children are very fast to experience fatigue. While the level of muscle strength of children mentally disabled with normal children is also different, where mentally disabled tired faster than normal children.Keywords: Power, Leg Muscle, Mentally Disable.